Elevating Green Business and Product on Small Business: Impact of Green Entrepreneurship Motivation, Green Operation Management, and Green Marketing - Nusraningrum, Dewi; Widyanty, Winda; Wulandari, Ririn (Journal of Ecohumanism, 2024)
Small businesses with insights into the market potential for green products in the densely populated Capital region of Indonesia and its surroundings, encourage investment and innovation in developing new green products and understand the contribution of promoting environmental sustainability and strengthening a sustainable green economy in the region. Small entrepreneurs with limited investment have green entrepreneurship motivation and a green orientation to preserve the environment in populated cities, yet they must be exposed. Data were collected through online and in-person questionnaire distribution. The questions discuss green entrepreneurship motivation, green operations management, green business, green products, and green marketing in small businesses 358. The data was processed using SEM-PLS. The motivation of green entrepreneurs is proven to influence the management of green operations, businesses, products, and marketing. It has also been proven that green operations management, business, and marketing can mediate green Entrepreneurship motivation. Green Entrepreneurship motivation can increase the tied variables studied. Green businesses and products need to be nurtured by stakeholders so that small entrepreneurs care about sustainability. This research needs to be carried out on an ongoing basis throughout Indonesia to provide a complete research model